Predicting happiness based on self-differentiation mediated coping styles in obese men and women - Vahidi, Shaghayegh; Aghausefi, Alireza; Namvar, Hooman (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to predict happiness based on self-differentiation in obese individuals through mediation of coping styles in obese men and women. Methods: The present research method is descriptive-correlation. The statistical population of the present study included people with obesity who referred to counseling and psychology centers in District 1 of Tehran in 2021. The study included 210 people from the community who were selected using available sampling method. Data were obtained using the Oxford Happiness Questionnaire (Argyle and Lowe, 1990), the Self-Differentiation Questionnaire (Scorron and Friedlander, 1998), and the Coping Styles Questionnaire (Andler and Parker, 1990). The collected data were analyzed using structural equation modeling method and Amos software version 22. Results: Coping styles (B = 0.02; P